2006
DOI: 10.1038/ng1959
|View full text |Cite
|
Sign up to set email alerts
|

PALB2, which encodes a BRCA2-interacting protein, is a breast cancer susceptibility gene

Abstract: PALB2 interacts with BRCA2, and biallelic mutations in PALB2 (also known as FANCN), similar to biallelic BRCA2 mutations, cause Fanconi anemia. We identified monoallelic truncating PALB2 mutations in 10/923 individuals with familial breast cancer compared with 0/1,084 controls (P = 0.0004) and show that such mutations confer a 2.3-fold higher risk of breast cancer (95% confidence interval (c.i.) = 1.4-3.9, P = 0.0025). The results show that PALB2 is a breast cancer susceptibility gene and further demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
764
7
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 863 publications
(824 citation statements)
references
References 14 publications
38
764
7
15
Order By: Relevance
“…According to this model, genetic susceptibility to breast cancer is explained by the effects of BRCA1 and BRCA2 mutations, and the residual familial clustering is explained by the joint multiplicative effect of a large number of genes each of small effect (i.e., by a polygenic component). Direct evidence for the polygenic basis of the residual familial clustering not due to BRCA1 and BRCA2 mutations has more recently been provided by the identification of further loci that confer moderate risks, including mutations in CHEK2, ATM, PALB2, BRIP1 (The CHEK2 Breast Cancer Case -Control Consortium, 2004;Renwick et al, 2006;Seal et al, 2006;Rahman et al, 2007) and the low-risk variants identified through genome-wide or candidate gene association studies Easton et al, 2007;Hunter et al, 2007;Stacey et al, 2007).…”
mentioning
confidence: 99%
“…According to this model, genetic susceptibility to breast cancer is explained by the effects of BRCA1 and BRCA2 mutations, and the residual familial clustering is explained by the joint multiplicative effect of a large number of genes each of small effect (i.e., by a polygenic component). Direct evidence for the polygenic basis of the residual familial clustering not due to BRCA1 and BRCA2 mutations has more recently been provided by the identification of further loci that confer moderate risks, including mutations in CHEK2, ATM, PALB2, BRIP1 (The CHEK2 Breast Cancer Case -Control Consortium, 2004;Renwick et al, 2006;Seal et al, 2006;Rahman et al, 2007) and the low-risk variants identified through genome-wide or candidate gene association studies Easton et al, 2007;Hunter et al, 2007;Stacey et al, 2007).…”
mentioning
confidence: 99%
“…210,211 In addition, germline mutations in RAD51C and RAD51D, more recently shown to interact with the Fanconi pathway 212 as well as RAD51 and the BRCA1 co-factor BARD, have all been associated with predisposition to breast and/or ovarian cancer. [213][214][215] These findings, revealing defects in the Fanconi pathway beyond BRCA1/2 mutations to be associated with cancer risk, advocate disturbances in other Fanconi complex components to be examined with respect to drug sensitivity/resistance as well (see below).…”
Section: Homologous Recombination Repairmentioning
confidence: 99%
“…Further, genetic linkage analyses failed to identify additional high-penetrance susceptibility genes and the identification of rare variants of genes involved in DNA repair, such as CHEK2, ATM, BRIP and PALB2 in families lacking BRCA mutations (Meijers-Heijboer et al, 2002;Thompson et al, 2005;Rahman et al, 2007;Hollestelle et al, 2010), associated with a moderate risk of disease, can explain only a small portion of familial risk.…”
Section: Introductionmentioning
confidence: 99%